INFORMATION ON THE DESIGN OF FAILURE COMPLEX DETECTION HOUSE - Rubbie Himawan; Indrianto. Skom. MT Indrianto. Skom. MT (Jurnal Sistem Komputer, 2002)
Lack of attention to the developers of housing complexes in the matter of light,causing less terawatnya this facility. Thus we sometimes see in a housing complexthere are some lighting that is not functioning or damaged. If there are no complaintsfrom the residents, will require a long time to fix it or may not be completelyrepaired.Given the problems above, required a lighting failure detection system that canmonitor all the existing lighting at a housing complex. In this case, the authors use the8255 Programmable Peripheral Interface as an interface (interface) as a lightcontroller that uses the Turbo C as software that provides information to the operatortentrang housing complex lighting conditions.